The right call : what sports teaches us about work and life - Jenkins, Sally (Gallery Books, 2023)
"Sportswriter and columnist Sally Jenkins spent her whole life literally stamping great coaches and athletes down in letters. But somewhere along the line, she realized, they had begun to write her. Their example could shape her into something better if she paid attention. What she learned from great athletes and coaches is that champions are the product of their own work. This book is an effort to catalog the inner qualities that allow ordinary people to overcome pressure, elevate their performances and find champion identities. THE RIGHT CALL uses breath-takingly dramatic sports anecdotes featuring the elite coaches and play-makers Steve Kerr, Bill Belichick, Pat Summit, Peyton Manning, and Jill Ellis, Michael Phelps, and Andre Agassi, among others, to illustrate 7 principles which underlie great decision-making. The seven principles (conditioning, practice, discipline, candor, culture, resilience, intention) are each broken down and explored in their own chapters through long-form sports stories. This book is the one stop shop for anyone wanting to learn how to effectively lead and achieve. From sports fans to businesspeople and everyone in between, there is something for any reader ready to elevate their greatness practices"--